The pearl of days - Farquhar, Barbara H. (Barbara Henry), 1815-1875; Whymper, Elijah, active 1848-1863 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Pearl of Days: or, The Advantages of the Sabbath to the Working Classes" by a Labourer's Daughter is a social and religious essay written in the mid-19th century. This work focuses on the significance and benefits of Sabbath observance, particularly for working-class people. The central theme is the argument that the weekly day of rest is essential not only for spiritual well-being but also for moral, intellectual, and social improvement among laborers and their families. Its perspective is both practical and inspirational, blending personal experience with societal critique. The opening of the book includes a poetic dedication and introductory material that situate the essay within its historical and social context. There is a preface from an American clergyman emphasizing the essay$1 (Bs unique perspective$1 (Bwritten by someone from the working class$1 (Band endorsing its lessons for parents, reformers, and workers. The introduction recounts how the essay originated in response to a literary competition for laborers, and highlights the remarkable voice and life story of the female author. The initial pages of the essay itself explore the formative role of the Sabbath in the author's own upbringing, describing how her family, despite poverty and hard work, used Sunday for rest, religious education, and self-improvement. These sections set the tone for the main argument: that the Sabbath is a cornerstone for personal and social advancement, especially among the working classes. (This is an automatically generated summary.)s
Release date is 2025-05-06
Mairi and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Christian life; Sunday; Sabbath; Christian literature; Didactic literature; Working class -- Conduct of life